Land Archive Authentication as a Result of Media Transfer at the Land Office - Pramesti, Natasha Ajeng; Junarto, Rohmat; Farid, Abdul Haris (Marcapada: Jurnal Kebijakan Pertanahan, 2023)
The digitalization efforts undertaken by the land office do not necessarily guarantee the authenticity of its records or documents in the same manner as physical documents. Authentication is essential to reinforce the utility of digital land documents and bestow legal validity as admissible evidence in court. This research aims to analyze the implementation of digitalization and authentication of land documents at the land office. Furthermore, the analysis discusses the necessity of authenticating digital land documents to ensure that the resulting products can serve as valid evidentiary tools in legal proceedings. This research employs a descriptive qualitative approach. The study reveals that the execution of digitalization and authentication of land documents at the WG Land Office does not comply with Law No. 43 of 2009, Government Regulation No. 28 of 2012 concerning archiving, Head of the National Archives of the Republic of Indonesia Regulation No. 20 of 2011 on guidelines for authenticating electronic archives, and the Circular Letter of the Ministry of ATR/BPN No. 5/SE-100.TU.02.01/VIII/2019 on digitization standardization of warkah. In pursuit of legal certainty that aligns with formal legal truth, including the interests of all parties involved, the authentication of digital land documents as a source of juridical data is paramount in assessing and adjudicating a case before a panel of judges.